Propagation of computer virus both across the Internet and external computers: A complex-network approach - Gan, Chenquan; Yang, Xiaofan; Liu, Wanping; Zhu, Qingyi; Jin, Jian; He, Li (Communications in nonlinear science & numerical simulation, 2014)
•This paper addresses the effects of the Internet topology and external computers on computer virus spreading.•An epidemiological model is established.•The unique (viral) equilibrium of the model is globally attractive.•Computers with higher node degrees are more susceptible to infections than those with lower node degrees.•Some appropriate protective measures are suggested. Based on the assumption that external computers (particularly, infected external computers) are connected to the Internet, and by considering the influence of the Internet topology on computer virus spreading, this paper establishes a novel computer virus propagation model with a complex-network approach. This model possesses a unique (viral) equilibrium which is globally attractive. Some numerical simulations are also given to illustrate this result. Further study shows that the computers with higher node degrees are more susceptible to infection than those with lower node degrees. In this regard, some appropriate protective measures are suggested.